Automatic control of process of design of the asynchronous muff with ferromagnetic cartridge on the secondary rotor - Красношапка, М. Д; Казак, В. Н.; Мазур, Т. А. (Problems of Informatization and Control, 2009)
The design procedure of optimum parameters asynchronous муфты with a ferromagnetic sleeve on a conducted rotor is offered. For this purpose we have applied search methods of optimization with performance of restrictions on a kind of the mechanical characteristic